Modulating the Microenvironment of Coumarin Dyes within Multihierarchical Supraparticles: En Route toward Versatile Luminescent Dual-Threshold Temperature Indicators with Ratiometric Readout - Reichstein, Jakob; Luthardt, Leoni; Martello, Valentino Gabriel; Pianetti, Andrea; Wintzheimer, Susanne; Mandel, Karl (Advanced Optical Materials, 2024)
Temperature indicators trace (un)desired thermal impacts across their thermal history upon readout at every point of interest via defined irreversible signal changes. Ratiometric luminescent temperature indicators are attractive due to their fast, sensitive, contactless, spatially-resolved, and self-referenced readout. However, they have a limited working range as commonly only one specific temperature-induced physicochemical effect is exploited. Herein, dual-threshold temperature indicator supraparticles (SPs) are introduced that expand the working range of individual luminescent probes and enhance the extractable information on the thermal history. These SPs derive their functionality from the synergistic interplay of three spectrally distinguishable luminescent species assembled in one multihierarchical, micrometer-sized particle of hybrid organic-inorganic nature. This engineered nanostructure enables the stepwise modulation of the physicochemical microenvironment of two incorporated coumarin species at programmable threshold temperatures, resulting in distinct changes in their emission. As these changes are based on dye-specific mechanisms that are induced in consecutive temperature regimes, the SPs achieve a scarcely reported broad working range (60–200 °C) with temperature-dependent response times of minutes to seconds. From a broader perspective, the conceptualized SPs pioneer in how multiple individual luminescent probes with different excitation-emission properties and indicator mechanisms are synergistically united in one advanced indicator system by precise material engineering.<br
Keywords: luminescence; nanoparticles; sensors; supraparticles; temperature indicators